Improving outcomes for hospital patients with critical bleeding requiring massive transfusion: the Australian and New Zealand Massive Transfusion Registry study methodology. (December 2016) - Oldroyd, J.; Venardos, K.; Aoki, N.; Zatta, A.; McQuilten, Z.; Phillips, L.; Andrianopoulos, N.; Cooper, D.; Cameron, P.; Isbister, J.; Wood, E.
Abstract Background The Australian and New Zealand (ANZ) Massive Transfusion (MT) Registry (MTR) has been established to improve the quality of care of patients with critical bleeding (CB) requiring MT (≥ 5 units red blood cells (RBC) over 4 h). The MTR is providing data to: (1) improve the evidence base for transfusion practice by systematically collecting data on transfusion practice and clinical outcomes; (2) monitor variations in practice and provide an opportunity for benchmarking, and feedback on practice/blood product use; (3) inform blood supply planning, inventory management and development of future clinical trials; and (4) measure and enhance translation of evidence into policy and patient blood management guidelines. The MTR commenced in 2011. At each participating site, all eligible patients aged ≥18 years with CB from any clinical context receiving MT are included using a waived consent model. Patient information and clinical coding, transfusion history, and laboratory test results are extracted for each patient's hospital admission at the episode level. Results Thirty-two hospitals have enrolled and 3566 MT patients have been identified across Australia and New Zealand between 2011 and 2015. The majority of CB contexts are surgical, followed by trauma and gastrointestinal haemorrhage. Validation studies have verified that the definition of MT used in the registry correctly identifies 94 % of CB events, and that the median time of transfusion for the majority of fresh products is the 'product event issue time' from the hospital blood bank plus 20 min. Data linkage between the MTR and mortality databases in Australia and New Zealand will allow comparisons of risk-adjusted mortality estimates across different bleeding contexts, and between countries. Data extracts will be examined to determine if there are differences in patient outcomes according to transfusion practice. The ratios of blood components (e.g. FFP:RBC) used in different types of critical bleeding will also be investigated. Conclusions The MTR is generating data with the potential to have an impact on management and policy decision-making in CB and MT and provide benchmarking and monitoring tools for immediate application.